Le prix payé - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
OugandaTABB0, 15-0, 30Nlle-ZélandeTABB0, 16Sénégal 0, 23-0, 30Etats-UnisTABB0, 30Jamaïque 0, 33-0, 45FidjiTABB0, 35Union européenneTABB0, 39Sources